(untitled) (EUROPEAN AND ASIAN LAW REVIEW, 2025)
The article conducts a theoretical analysis of the fundamental differences between labor and civil law relations, the identification of which is important in the judicial practice of establishing the nature of de facto legal relations. Specific scientific approaches to their content and regulatory capabilities are considered. Definitions of personal labor, hired labor, private labor, production organizer and labor relations are substantiated and proposed. The law enforcement practice of the Russian Federation in recent years regarding the court’s recognition or non-recognition of de facto legal relations as labor relations is assessed. An analysis of the regulatory legal acts of the countries of the Eurasian Economic Union (Armenia, Belarus, Kazakhstan, Kyrgyzstan and Russia) is carried out, using which national models of labor relations are revealed and compared. The logical conclusion of the analysis is the necessity of introducing legislative amendments that combine a balance between regulatory flexibility and ensuring legal certainty.